"Transpiration and crop yields" by C.T. de Wit, 1958, Institute of biological and chemical research of field crops and herbage, No. 64.6, Wageningen, the Netherlands. Issue 1 (9th March 2020) - Sinclair, Thomas R.
Abstract: This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by C.T. de Wit published in 1958 that explored the relationship between transpiration and crop growth. He organized his analysis data from experiments from a range of environments, many of which were done early in the 20th century. He found that there was a very high correlation within a species between growth and transpiration normalized for pan evaporation over a wide range of conditions, and the slope of the relationship was distinct for each species. He examined possible variation in the slope to growth conditions and found the slope remained essentially constant. Thus, he concluded that there was an intimate, stable dependence for each crop species on the amount of water lost and its growth.